Competitiveness of the Peruvian fishing sector in the international market, 2014-2023 - Bueno Gonzales, Daniela Elizabeth; Karen Yovana, Huanca lezcano; Montes Tocto, Richard Ignacio; Collazos Alarcón, Mercedes Alejandrina (LACCEI, 2025)
This study analyzes the level of competitiveness of the Peruvian fisheries sector between 2014 and 2023 using indicators such as Normalized Revealed Comparative Advantage (NRCV), Contribution to Trade Balance (ICTB) and the modified ECLAC competitiveness matrix. The results showed that Peru is competitive in four of five products: fishmeal, frozen squid, canned squid and fish oil. However, although it has a comparative advantage in almost all of its products, these have a low contribution to the trade balance during the period analyzed. In addition, the competitiveness matrix indicates that Peru maintains a relevant presence in countries with growing demand, except for fishmeal, where it has lost competitiveness to India. These findings suggest specialization in underperforming products such as frozen whole shrimp to strengthen its competitiveness and ensure a strong participation of the Peruvian fishing sector in the international market.